Segurança do paciente na percepção de docentes e discentes de graduação em enfermagem - Lopes, Mariana Neves de Araujo (2015)
Patient safety is a concern of health professionals, particularly nursing, as the professional care, which is closest to the patient and performs procedures, being more susceptible to preventable errors and irreversible damage. Objectives: To identify the knowledge on the subject patient safety, disciplines, teaching-learning strategies and beliefs of students and teachers in the development of this subject in undergraduate nursing courses. Method: A descriptive, cross-sectional study with a quantitative approach, with the first part of the research being carried out with 167 students of third and fourth years, through a questionnaire, which consisted of two parts: the first was to characterize the subjects, and the second part contained issues related to patient safety setting according to the WHO, subjects related to this content, and evaluation of strategies, first contact with the patient in clinical practice and before that contact received theoretical and laboratory support, if witnessed some adverse event during the course and feel safe to perform the techniques and procedures inherent to the profession. The second survey was conducted with 51 nursing teachers, through a questionnaire, which included the characterization of the subject and issues related to patient safety setting according to the WHO, subjects presenting that content and strategies used in the teaching-learning process and they have caused some adverse event during working life. It was also found in both questionnaires the knowledge of each of the 10 steps to patient safety described in 2010. COREn the primer For inferential analysis of quantitative variables we used the Student's t test. As for comparisons of frequencies, involving the nominal qualitative variables, we used chi-square test. Results: In the first study between the two institutions the students said they knew the subject, but less than 40% got the patient's security setting, with significant differences between institutions and more than 60% missed the concept of each of the 10 steps for security, with no significant difference between the institutions. In the second study, there was disagreement as to the knowledge of the concepts, teaching strategies and experience of teachers, with the highest number of hits in a private institution. In both studies, the majority says he knows the subject, but missed the definition and measures of good practice in each of the 10 steps of Coren's playbook. Conclusions: It was found the absence of specific discipline and insufficient knowledge about this subject matter on the part of teachers and students, therefore, this study helped foster the need to subject the inclusion in nursing undergraduate courses in order to improve the training of nurse.